Pannexin 1 role in the trigeminal ganglion in infraorbital nerve injury‐induced mechanical allodynia. (23rd January 2022) - Kurisu, Ryoko; Saigusa, Tadashi; Aono, Yuri; Hayashi, Yoshinori; Hitomi, Suzuro; Shimada, Masahiko; Iwata, Koichi; Shinoda, Masamichi
Abstract: Objectives: The detailed pathological mechanism of orofacial neuropathic pain remains unknown. We aimed to examine the pannexin 1 (Panx1) signaling in the trigeminal ganglion (TG) involvement in infraorbital nerve injury (IONI)‐induced orofacial neuropathic pain. Materials and Methods: Mechanical head‐withdrawal threshold (MHWT) was measured in IONI‐treated rats receiving intra‐TG Panx1 inhibitor or metabotropic glutamate receptor 5 (mGluR5) antagonist administration and MHWTs in naive rats receiving intra‐TG mGluR5 agonist administration post‐IONI. Glutamate and Panx1 in the TG were measured post‐IONI. Panx1, mGluR5, and glutamine synthetase expression in TG were immunohistochemically identified, and changes in the number of mGluR5‐P2X3 ‐expressed TG neurons were examined. Results: MHWT was significantly decreased post‐IONI, and this decrease was reversed by Panx1 inhibition or mGluR5 antagonism. mGluR5 agonism induced a decrease in the MHWT. IONI increased extracellular glutamate in TG. Panx1 was expressed in satellite glial cells and TG neurons, and intra‐TG mGluR5 antagonism decreased the number of mGluR5 and P2X3 positive TG neurons post‐IONI. Conclusions: IONI facilitates glutamate release via Panx1 that activates mGluR5 which was expressed in the nociceptive TG neurons innervating the orofacial region. In turn, P2X3 receptor‐expressed TG neurons are enhanced via mGluR5 signaling, resulting in orofacial neuropathic pain.